Myanmar Economic Monitor, June 2020 : Myanmar in the Time of COVID-19 - World Bank (World Bank, Washington, DC, 2020)
The Covid-19 (coronavirus) pandemic has interrupted Myanmar’s economic expansion, and while Myanmar is expected to narrowly escape a recession, helped by a strong start to the fiscal year, policy responses, and the limited disease outbreak, the growth recovery is at great risk. Myanmar’s GDP growth is estimated to drop from 6.8 percent in FY2018/19 to 0.5 percent in FY2019/20. Following strong activity in the first five months of the year, the pandemic and associated containment measures are undermining aggregate demand, disrupting value chains, and reducing the labor supply. The crisis has had an especially negative effect on wholesale and retail trade, tourism-related services, manufacturing, and construction, though weakening consumer demand is also projected to ease inflationary pressures in FY2019/20. Under the baseline scenario, Myanmar’s GDP growth rate is projected to rise to 7.2 percent in the medium term, assuming that the domestic spread of the virus is brought under control, the impacts of the government’s small but targeted Covid-19 Economic Relief Plan (CERP) materialize, and the global economy recovers. The anticipated recovery will be supported by rising investment in infrastructure and services, rebounding exports, and increased private consumption. However, risks to this year’s growth estimate and the outlook are tilted heavily to the downside, as the unpredictable evolution of the pandemic could delay the resumption of economic activity. In all scenarios, severe damage to the operation of firms and the welfare of households is expected to pose serious risks to Myanmar’s remarkable progress on poverty reduction.